Scarlet Fever with Hepatitis - Rethy Swastriayuri Wijaya; M Fahrul Udin (Muhammadiyah Medical Journal, 2026)
Background: Scarlet fever is an infection of toxin-producing Group A Beta-Hemolytic Streptococcus (GABHS) bacteria, usually presenting as a tonsillopharyngitis with spreading maculopapular rash originating from the trunk. The World Health Organization (WHO) has reported multiple outbreaks in multiple countries in recent years. It most commonly affects school-age and adolescent children. It has a good overall prognosis with proper antibiotic treatment and well-documented complications. Case Report: We present a case of a 12-year-old boy with typical manifestations of scarlet fever, but with abnormally elevated liver enzymes, suggesting a possible hepatic involvement with this disease. Hepatitis secondary to scarlet fever has been reported previously, though it remains rare, especially in pediatric patients. But even so, it has been recognized as a benign entity. The pathophysiologic mechanisms underlying these two diseases remain poorly understood. Conclusion: This case is reported to raise awareness among healthcare providers of this rare but important complication of scarlet fever.